Assessing the Impact of Green Building Certifications on Construction Practices in Nigeria: A Systematic Review - Unegbu, Hyginus; YAWAS, Danjuma S. (Indonesian Journal of Engineering and Technology (INAJET), 2024)
This study analyzes the impact of green building certifications on construction practices in Nigeria, focusing on LEED, EDGE, and BREEAM. Using a systematic review of literature from 2015 to 2023, it evaluates certification adoption, changes in construction practices, and economic and environmental outcomes. Key findings show limited but growing certification adoption driven by international standards and local initiatives. Certified buildings in Nigeria exhibit improvements in energy efficiency, water conservation, and waste reduction, leading to enhanced sustainability and lower operational costs. However, barriers such as high initial costs, a shortage of skilled professionals, and insufficient government policies hinder progress. The study emphasizes the need for stronger governmental support, increased public awareness, and the development of local industries for sustainable materials. Future research should explore the long-term economic benefits of green buildings, barriers to adoption, and comparative studies with other developing nations. This research provides insights for policymakers, developers, and stakeholders to promote green building practices in Nigeria, aligning with global sustainability goals.